CLASSROOM INTERACTION AND MEANS OF FORMATIVE ASSESSMENT IN THE ENGLISH LANGUAGE LESSONS - Kosmurat Akhbota; Kudaibergenova M.R; Kairbaeva A.K (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In modern research, the assessment method is considered, first of all, as a technology of pedagogical assessment in the educational process, which provides an individual approach to learning, takes into account the capabilities and needs of students, develops their ability to work independently with information sources and the development of educational material, contributes to the systematization of the entire learning process.